A new gaming platform to improve cognitive performance and promote healthy behavior: a pilot study. (30th September 2020) - Baccolini, V; Isonne, C; Migliara, G; Salerno, C; Marzuillo, C; De Vito, C; Villari, P; Romano, F
Abstract: Background: Brain training games can sharpen the mind and potentially prevent cognitive diseases, that are particularly relevant to the population ageing. The EU funded project ACDC, Adult Cognitive Decline Conscientiousness, developed an online training tool to train cognitive functions and promote healthy behaviors in the adult population. Methods: An online platform, consisting of 16 games with different levels, was built. Three main brain domains were targeted: memory, visuospatial and verbal skill. After the completion of each game level, healthy lifestyle tips were presented to the users. Participants were actively recruited from the project partners; inclusion criteria were adult age (40-70 years) without cognitive diseases. An adapted version of the Montreal Cognitive Assessment was used to assess cognitive performance at the start and after two hours of active gaming. The paired t-test was used to compare the scores before and after the training. A satisfaction questionnaire was administered at the end of the training session. Results: Fifty-six participants from three European countries (Austria, Spain and Italy) took part in the pilot phase (median age: 57, IQR: 47-66). Most of them were university graduates (38%) or had a high school diploma (41%), employed full-time (46%) and females (82%). Significant improvements were registered in the verbal domain, where the mean score increased from 4.18 to 4.83 (p = 0.047), and in the memory area, where the mean score grew from 4.80 to 6.60 (p < 0.001). The visuospatial mean score improved from 4.55 to 5.16 (p = 0.0518). Most users (84%) were greatly satisfied with the platform and reported a high level of appreciation for the interactive gaming approach. Conclusions: Despite the small sample size, the pilot phase detected some improvements in cognitive performance and a good appreciation of the training tool. Given these encouraging findings, the study will now be extended to more participants. Key messages: The newly developed platform represented a promising tool to train cognitive functions. The proposed interactive gaming approach was greatly appreciated by the users.